PENGARUH WORD OF MOUTH, PENGALAMAN BELANJA ONLINE, PERSEPSI KEMUDAHAN, DAN PERSEPSI RESIKO TERHADAP MINAT BELANJA KONSUMEN DI SITUS JUAL BELI ONLINE LAZADA (Studi Kasus Pada Mahasiswa UNISMA Fakultas Ekonomi Dan Bisnis Jurusan Manajemen JL.MT.Haryono 193 Malang) (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research is meant to find the effect of word of mouth, online shopping experience, perceived ease and perceived risk of interest shopping. The sampling technique was conducted by purposive sampling method. The data used in this study is primary data. This type of research belong to explanatory research. The population of this current study was all university students in economy major at UNISMA who had fulfilled the registration fee. Data analysis method used in this research is using multiple linier regression analysis with t test hypothesis. The result of this study indicate that partially online shopping experience and perceived risk significant effect on interest shopping. While word of mouth and perceived ease partially no significant effect on interest shopping.Keywords : word of mouth, online shopping experience, perceived ease,  perceived risk, interest shopping